Determinants of cross-border bank acquisitions in transition economies: a latent class analysis - Tigran Poghosyan; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2008)
We analyze the microeconomic determinants of cross-border bank acquisitions in 16 transition economies over the period 1996-2006. By using a latent class discrete choice model we explicitly incorporate the macroeconomic and institutional heterogeneity of the transition economies into our analysis. We find that foreign banks target relatively large and efficient banks when they enter transition economies with weak institutions. This evidence provides support for the market power hypothesis. However, when foreign banks enter more developed transition economies that have made progress in economic reform, they acquire less efficient banks. This result is in line with the efficiency hypothesis.
Keywords: G21; G34; E44; F21; 330; Cross-border bank acquisitions; latent class logistic model; transition economie; Internationale Bank; Übernahme; Ausländisch; Bank; Wirtschaftliche Effizienz; Übergangswirtschaft; Osteuropa